A Cascade Analysis for the IceCube Neutrino Telescope - Hickford, Stephanie Virginia (University of Canterbury. Physics and Astronomy, 2012)
IceCube is the largest operating neutrino observatory. An array of photomultiplier tubes deployed throughout a cubic kilometre of the Antarctic ice at the South Pole detect the Cherenkov radiation from neutrino-nucleon interactions. IceCube is capable of detecting neutrinos over a large energy range. The physics manifesto includes dark matter searches, cosmic ray observation, all sky point source searches, and particle physics parameter constraints. Astrophysical neutrinos are expected to originate from hadronic interactions in some of the most energetic regions in the Universe. The detection of high energy astrophysical neutrinos will provide direct information about the astrophysical sources that produced them. This thesis concentrates on the cascade channel for neutrino detection. Two separate studies are performed; a high energy cascade analysis and a parameterisation of the production of muons within hadronic cascades. The experimental data for the cascade analysis was taken by IceCube from April 2008 to May 2009 when the first 40 IceCube strings were deployed and operational. The analysis was designed to isolate the astrophysical neutrino signal from the atmospheric and muon background. Fourteen cascade-like events were observed, on a background of 2.2 ⁺⁰·⁶ ₋₀·₈ atmospheric neutrino events and 7.7 ± 1.0 atmospheric muon events. This gives a 90% confidence level upper limit of ΦlimE²≤ 7.46 × 10⁻⁸ GeVsr⁻¹s⁻¹cm⁻² , assuming an E⁻² spectrum and a neutrino flavour ratio of 1 : 1 : 1, for the energy range 25.12 TeV to 5011.87 TeV. Decay of hadronic particles in cascades produces muons. If the muons are energetic enough they can significantly alter the topology of the cascade and hence the reconstruction of the event in an analysis. The production of high energy muons within hadronic cascades was simulated and parameterised using Pythia and GEANT simulation programs.